Kinetics and Mechanism of bromination of 1-Hetera-4-Cyclohexanones by N-Bromobarbitone - Jambulingam, M.; Murugesan, M.; Rajeswari, A.; Satish, Asha (Asian Journal of Chemistry, 2010)
Kinetics of bromination of substituted 1-hetera-4-cyclohexanones by N-bromobarbitone [NBB] has been studied in aqueous acetic acid medium in the presence of HCIO4 and mercuric acetate. The reaction is acid and mercuric acetate catalysed exhibiting first order dependence each in [acid], [Hg(OAc)2] and [substrate] and zero order in [NBB]. This supports the acid catalysed enolisation of ketone as the rate determining step and reaction between enol and NBB as the first step. The decrease in dielectric constant of the medium enhances the rate of reaction. Arrhenius activation parameters have been computed. A plausible mechanism based on these observations is proposed. The effect of the various substituents on the rates of bromination has been rationalized on the basis of their inductive and steric effects,